Scenario of endometrial cancer in Asian countries: epidemiology, risk factors and challenges - Sultana, Sayeeda; Parveen, Rehana (International Journal Of Community Medicine And Public Health, 2025)
Endometrial cancer is one of the commonest gynecological malignancies which has been widely studied in West; however, it is on a rise throughout Asia owing to westernization of lifestyle, population ageing and rising prevalence rate of obesity. The aim of this review is to provide a comprehensive analysis of endometrial cancer epidemiology, risk factors, treatment challenges and healthcare disparities studies among Asian countries with key recommendations on how detection and prevention efforts could be enhanced in the region. A systematic review using databases such as PubMed and Scopus to find studies from 2000 until 2023. Inclusion criteria included epidemiological data, risk factors and access to health care on endometrial cancer in Asia. Screening of articles; extraction of relevant data on incidence, mortality rates, risk factors and barriers to healthcare. The incidence of endometrial cancer throughout Asia is heterogeneous; Japan (10.2/100,000) and Singapore (13.1/100,000) have similar rates to countries in the West while India (3.2/100,000) and Indonesia (3.5/100,000) have rates that are lower than expected. Obesity, one of the key risk factors accounting for 27–35% of urban populations, metabolic syndrome and postponement to childbirth are among them. In low-income nations, the access to more sophisticated therapy like minimal invasive surgery is 45% limiting survival for overbuilt-drugs resistant bacterial infection cases whose mortality is more than 80% in high-income countries but less than 50% in resource-constrained settings. Modifying traditional behavioral and religious practices affecting recognition of symptoms, access to medical services and public awareness on endometrial cancer will likely alleviate the burden of this malignancy across Asia.